Application and Mechanism of Electrical Neuromodulation Techniques for Rehabilitation of Spinal Cord Injury - LIU Wenhui; SUN Wenting; HU Naichong; LI Yanpi; WANG Zhenghui (康复学报)
Spinal cord injury (SCI) is a serious neurological disease, which often leads to severe impairments of motor, sensory and autonomic nervous functions. Electrical neuromodulation techniques have shown broad application prospects in the rehabilitation treatment of SCI. This study reviewed the applications and possible mechanisms of electrical neuromodulation techniques in the rehabilitation after SCI. It mainly introduced the applications of invasive techniques [spinal cord stimulation (SCS) and deep brain stimulation (DBS) ] and non-invasive techniques [peripheral nerve stimulation (PNS) and transcranial direct current stimulation (tDCS)] in the rehabilitation after SCI. The mechanisms of electrical neuromodulation techniques in the treatment of SCI may be The mechanisms of electrical neuromodulation techniques in the treatment of SCI may be related to the regulation of synaptic plasticity to promote nerve regeneration and repair, the regulation of neurotransmitter system to improve the cascade of inflammatory response, and the regulation of neural network excitability to promote the reconstruction of neural circuits. Electrical neuromodulation techniques can improve motor and autonomic nervous functions after SCI to a certain extent, but they are still unable to quickly provide the most suitable personalized treatment plans for various types of SCI; there is no consensus on the specific parameters of stimulation frequency, intensity, duration and waveform for different levels of SCI. The future research should continue to analyze the efficacy and specific mechanisms of different interventions on neurological dysfunction after SCI at different levels, and adopt multimodal and individualized regulation programs; explore the key principles of electrical signals in the recovery of motor and sensory functions after SCI, and formulate an expert consensus on the application of electrical neuromodulation techniques according to the type of spinal cord segment injury, age and gender, so as to provide a reference for the application of electrical neuromodulation techniques in the rehabilitation of patients with SCI.